2019
DOI: 10.3389/fphar.2019.00760
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Inhibits Androgen Production in Rat Immature Leydig Cells

Abstract: Background: Propofol is a widely used anesthetic. Whether propofol inhibits androgen production by rat Leydig cells and the underlying mechanism remains unclear. The objective of the current study was to examine the effects of propofol exposure to rat primary immature Leydig cells and to define propofol-induced inhibition of steroidogenic enzymes in both rat and human testes in vitro . Methods: Immature Leydig cells were purified from 35-day-old male Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Recent studies have found that various anesthetics might have the potential to affect LC functions directly or indirectly ( 50 , 66 68 ). However, most of these studies focused on acute effects on well-developed adult LCs, not on the development of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that various anesthetics might have the potential to affect LC functions directly or indirectly ( 50 , 66 68 ). However, most of these studies focused on acute effects on well-developed adult LCs, not on the development of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that various anesthetics might have the potential to affect LC functions directly or indirectly (50,(66)(67)(68). However, most of these studies focused on acute effects on well-developed adult LCs, not on the development of the cells.…”
Section: Discussionmentioning
confidence: 99%